Investigation of Phosphorescent Materials for Photovoltaic Device Applications - OLIVEIRA, MOACIR GOMES DE (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2019)
Phosphorescence is used in photovoltaic devices by embedding phosphorescence species within a transparent host polymer to absorb ultraviolet solar radiation followed by a slow emission of visible light. Phosphorescent material has come to the fore in luminescent applications as well light emitting and harvesting applications. Utilising long persistent phosphorescent energy converters in PV devices is just one avenue for improving the efficiency of the PV device under light and dark conditions. Combining these technologies in a passive approach can enhance the photovoltaic efficiency and effective energy transfer. The energy transfer from long persistent phosphors to the photovoltaic device has been investigated both to increase the fundamental understanding of the mechanisms and also with a view towards viable device applications. Concentration dependence of the spectroscopy and photoluminescence spectra of luminescent layers as well as quantum efficiency and photoluminescence decay has been investigated across the range of ultraviolet to visible light. It shows that a highly concentrated phosphorescent layer on top of the photovoltaic device is unable to satisfactorily enhance the photovoltaic efficiency under illumination. However, under dark conditions the efficiency can be significantly improved. During photoluminescence, the energy transfer from the luminescent layer is shown to increase the PV device power output and to also power a LED light for more than 5 minutes.
APPROVED
Keywords: Phosphorescent; Phosphorescence; After-Glow; Glow in the dark; Energy converter; Down Converter; Down conversion; Up conversion; Down Shifting; Luminescent; Luminescence; Battery; Polymer; Polysiloxanes; Solar panel; Renewable Energy; Energy storage; Solar power; Solar cell; Photovoltaic (PV); Phosphors